Market risk data analytics for selected Asian stock markets during the pandemic Covid-19 - Leng, Jing Teng; Chin, Wen Cheong; Lim, Min (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study investigates various conditional mean and variance models to account for the impact of COVID-19 on the selected Asian markets, specifically the Japanese and Singaporean stock markets. The research period (24 August 2012 to 24 August 2022) is split into two periods, from 24 August 2012 to 31 March 2020 and from 24 August 2012 to 24 August 2022, to analyse the effect of COVID-19 on both stock returns. We found that both returns exhibit non-normality. The best-fitted models for the Japanese and Singaporean stock markets are Student-t ARMA(1,1)-EGARCH(1,1) and ARMA(2,1)-GJR(1,1), respectively. The presence of the pandemic period indicates positive shifts in volatility intensity in both the Japanese and Singaporean stock markets. The 5% Value-at-Risk under the GARCH estimations is $3568.20 for Japan and $2050.40 for Singapore. Meanwhile, the 5% expected shortfall based on historical simulation for both countries is $3214.00 for Japan and $2196.26 for Singapore. From the results of Value-at-Risk and expected shortfall, the Japanese stock returns showed more significant maximum losses than Singaporean stock returns, which further indicates that the Japanese stock market was more volatile than the Singaporean stock market before and during the pandemic period.